2015
DOI: 10.1155/2015/984570
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cancer Pain by Targeting Cytokines

Abstract: Inflammation is one of the most important causes of the majority of cancer symptoms, including pain, fatigue, cachexia, and anorexia. Cancer pain affects 17 million people worldwide and can be caused by different mediators which act in primary efferent neurons directly or indirectly. Cytokines can be aberrantly produced by cancer and immune system cells and are of particular relevance in pain. Currently, there are very few strategies to control the release of cytokines that seems to be related to cancer pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 81 publications
0
28
0
3
Order By: Relevance
“…Several mechanisms have been postulated to explain the mechanisms underlying the carboplatin -induced toxicities such as production of reactive oxygen species (ROS), nitric oxide (NO) [3] and proinflammatory cytokines e.g. interleukin-1 (IL-1), interleukin-6 (IL-6) and tumor necrosis factor-α (TNFα) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been postulated to explain the mechanisms underlying the carboplatin -induced toxicities such as production of reactive oxygen species (ROS), nitric oxide (NO) [3] and proinflammatory cytokines e.g. interleukin-1 (IL-1), interleukin-6 (IL-6) and tumor necrosis factor-α (TNFα) [4].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recent research has indicated that cytokines play a key role in mediating cancer pain. 8 Infiltrating pro-inflammatory immune cells found within tumors, as well as cancer cells themselves, release cytokines, which bind to and sensitize neighbouring nociceptors to painful stimuli and elicit a central pain response. 8 Cancer is a systemic inflammatory state, and many of the symptoms experienced by cancer patients, including pain, can be attributed to the action of cytokines on the peripheral and central nervous systems.…”
Section: Introductionmentioning
confidence: 99%
“…8 Infiltrating pro-inflammatory immune cells found within tumors, as well as cancer cells themselves, release cytokines, which bind to and sensitize neighbouring nociceptors to painful stimuli and elicit a central pain response. 8 Cancer is a systemic inflammatory state, and many of the symptoms experienced by cancer patients, including pain, can be attributed to the action of cytokines on the peripheral and central nervous systems. 9 In healthy individuals, pro-and anti-inflammatory cytokines exist in equilibrium which is disrupted in the development of cancer, with patients showing both immuno-stimulatory and immunosuppressive profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The breast cancer is the second leading cause of death in women (1). It is estimated that by 2020, 70 percent of new cases of breast cancer will be observed in developing countries (2). The International Association for the Study of Pain (IASP) reported that the prevalent of pain in breast cancer is between 40% to 89% (3) and 17 million people complain of cancer pain.…”
Section: Introductionmentioning
confidence: 99%